Ursprung und Verbreitung der Paramo-Grasländer in Ostneuguinea - Löffler, Ernst (ERDKUNDE, 1979)
The high mountains of East New Guinea exhibit a distinctive geomorphology caused by the presence of glacial ice during the Pleistocene.The area covered by glacial ice usually coincides with the present day extent of the high altitude (paramo)grasslands. This coincidence is not due to climatic factors since the lower limit of the grasslands varies with the extent of the glaciation and extends to lower altitudes in mountains of a large massenerhebung than in mountains of only a small massenerhebung. The presence of grassland in the deep glacial troughs is thought to be primarily due to the high degree of wetness and not to the occurence of frost or cold air drainage. It is argued that the present day paramo grasslands in the New Guinea high mountains are quasi-natural. They owe their existence and extent to two main factors. Firstly, the effect of glacial erosion which has created the topographic conditions and with it the edaphic and eco logical conditions for the occurrence of natural valley-floor grasslands well below the upper timber line. Secondly, the effect of man who has visited these grasslands for several thousand years and has, through burning and felling, extended the grasslands from the valley floors to the adjacent slopes. Natural grasslands still occur in some of the more remote mountains and one example, Mt Digini in the Kubor Range is discussed.